Coordinate Metrology Accuracy of Systems and Measurements - Sładek, Jerzy A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book focuses on effective methods for assessing the accuracy of both coordinate measuring systems and coordinate measurements. It mainly reports on original research work conducted by Sladek's team at Cracow University of Technology's Laboratory of Coordinate Metrology. The book describes the implementation of different methods, including artificial neural networks, the Matrix Method, the Monte Carlo method and the virtual CMM (Coordinate Measuring Machine), and demonstrates how these methods can be effectively used in practice to gauge the accuracy of coordinate measurements. Moreover, the book includes an introduction to the theory of measurement uncertainty and to key techniques for assessing measurement accuracy. All methods and tools are presented in detail, using suitable mathematical formulations and illustrated with numerous examples. The book fills an important gap in the literature, providing readers with an advanced text on a topic that has been rapidly developing in recent years. The book is intended for master and PhD students, as well as for metrology engineers working at industrial and research laboratories. It not only provides them with a solid background for using existing coordinate metrology methods; it is also meant to inspire them to develop the state-of-the-art technologies that will play an important role in supporting quality growth and innovation in advanced manufacturing.
Keywords: Manufactures; Measurement; Measuring instruments; Computational intelligence; Machines, Tools, Processes; Measurement Science and Instrumentation; Computational Intelligence